2014
DOI: 10.1016/j.jcrysgro.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and properties of the non-centrosymmetric superconductor, Ru7B3

Abstract: We describe the crystal growth of high quality single crystals of the non-centrosymmetric superconductor, Ru 7 B 3 by the floating zone technique, using an optical furnace equipped with xenon arc lamps. The crystals obtained are large and suitable for detailed measurements, and have been examined using x-ray Laue patterns. The superconducting properties of the crystals obtained have been investigated by magnetisation and resistivity measurements. Crystals have also been grown starting with enriched 11 B isotop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…arXiv:1810.03876v1 [cond-mat.supr-con] 9 Oct 2018 It forms a NCS crystal structure with the space group P 6 3 mc [35], which is hexagonal in the basal plane. Our single-crystal sample has a superconducting transition temperature of T c = 2.6 K [36], which sits within the range of 2.5 to 3.4 K observed in earlier studies [37][38][39]. It is reported to have an isotropic s-wave gap [38], rather than the singlet-triplet mixture predicted for NCS superconductors.…”
Section: Introductionsupporting
confidence: 77%
“…arXiv:1810.03876v1 [cond-mat.supr-con] 9 Oct 2018 It forms a NCS crystal structure with the space group P 6 3 mc [35], which is hexagonal in the basal plane. Our single-crystal sample has a superconducting transition temperature of T c = 2.6 K [36], which sits within the range of 2.5 to 3.4 K observed in earlier studies [37][38][39]. It is reported to have an isotropic s-wave gap [38], rather than the singlet-triplet mixture predicted for NCS superconductors.…”
Section: Introductionsupporting
confidence: 77%
“…Almost three decades later, the absence of the inversion symmetry in its crystal structure was highlighted by Morniroli et al 22 . In various transport and thermodynamic measurements in the past 23 25 , it was seen that and 2 ) in Ru B were approximately 1.4 and 3.3, respectively, indicating a weak-coupling superconducting state. These measurements also indirectly indicated that a predominant fully gapped s -wave order parameter could describe the superconducting state of Ru B well.…”
Section: Introductionmentioning
confidence: 99%
“…Almost three decades later, the absence of the inversion symmetry in its crystal structure was highlighted by Morniroli et al [22]. In various transport and thermodynamic measurements in the past [23][24][25], it was seen that ∆C e /(γ n T c ) and 2∆ 0 /(k B T c ) in Ru 7 B 3 were approximately 1.4 and 3.3 respectively indicating a weak-coupling superconducting state. These measurements also indirectly indicated that a predominant fully gapped s-wave order parameter could describe the superconducting state of Ru 7 B 3 well.…”
mentioning
confidence: 98%